THE MANIFESTATION OF VARIETIES OF BLENDED LEARNING PEDAGOGY IN HIGHER EDUCATION - Safiah, Sidek; Massila, Kamalrudin; Razilah, A. Rahim (Journal of Human Capital Development (JHCD), 2017)
Despite the increased recognition on the use of online technologies for the delivery of flexible and student-centered learning environments, there are numerous critiques that its usage does not transform academic’s pedagogy: the uses of online technology for teaching and learning have been restrictive, mainly for dissemination or display of knowledge. This paper draws on the findings from three case studies that explore the manifestation of blended learning pedagogies in higher education. Six academics teaching at three different higher education contexts at two different countries, namely Australia and Malaysia were interviewed in order to understand the ways in which online technology is utilized for teaching and learning and the tensions arising from the usage. Guided by the perceptions that BLP is a socially situated practice, the study aims to interrogate the different manifestations of BLP at different contexts of higher education, highlighting the complex interplay between the users (academics), online technology and other significant elements within specific socio-cultural contexts. Focusing on the academic pedagogical practices that are shaped and reshaped within its specific socio-cultural context, this study demonstrates the complexity and fluidity of the different varieties of blended learning pedagogy that are manifested in different conditions and contexts. It contributes to further understanding of the ways in which online technologies are used in higher education pedagogy within the context of global knowledge economy that emphasizes flexible and student-centered pedagogy. Keywords: Blended Learning Pedagogy (BLP), higher education, online technology